184k views
5 votes
Which of the following show the expanded and simplified version of the expression

g(x) = 6(x + 2)2 + (x - 3)(x - 5)
a) 5x² + 16x +39
Ob) 7x² + 32x +39
Oc) 7x² + 16x +39
d) 7x² + 32x +9

User RaySF
by
5.6k points

1 Answer

3 votes

Answer:

c) 7x² + 16x +39

Explanation:

g(x) = 6(x + 2)² + (x - 3)(x - 5)

g(x) = 6(x² + 2*2x + 2²) + (x² - 3x - 5x + 15) =

= 6x² + 24x + 24 + x² - 8x + 15 = 7x² + 16x + 39

User Paolo Raez
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.